Cutaneous Necrotizing Vasculitis and Leukopenia in a Cocaine User: Is Levamisole the Culprit?. (7th August 2016) - El Khoury, Lara; Zeineddine, Nabil; Felix, Richard; Goldstein, Mark
Abstract : Levamisole is an antihelminthic drug banned by the US Food and Drug Administration (FDA) in 2000 because of its dangerous side effects. Over the past few years, it has been identified as an adulterant in cocaine and reported to cause cutaneous vasculitis in cocaine users. The health burden of levamisole is serious since it is estimated that over 5 million Americans use cocaine and that 70% of the cocaine used in the USA contains levamisole. In this paper we report the case of a 23-year-old female cocaine user that presented with purpuric rash and skin necrosis, found to have positive c-ANCA and anti-proteinase 3 antibodies. Her skin biopsy showed fibroconnective tissue with signs of necrosis, acute and chronic inflammation, and thrombus formation. She was diagnosed with levamisole-induced vasculitis and successfully treated with withdrawal of cocaine use and local wound care.